The Effect Of Benson Relaxation Technique on Anxiety Levels in Patients with Supraventricular Tachycardia (SVT) Who Will Undergo Cardiac Ablation - Firmansyah Satria Nugraha (Jurnal Kesehatan dr. Soebandi, 2025)
Anxiety is a state of mental state, personality, fear, premonition, feeling hopeless because of an imminent threat. In this study, the act of ablation is an invasive action that makes patients anxious. Benson's relaxation technique is a relaxation technique to lower anxiety levels. This study aims to determine the effect of the Benson relaxation technique on the level of anxiety in supraventricular tachycardia (SVT) patients who will perform ablation procedure at dr. Saiful Anwar Hospital, East Java Province. The research uses a pre-experimental design with a one-group pre-test post-test only design approach. The population was 36 patients and a sample of 30 respondents in total sampling method. This research was conducted in June-August 2024. The instrument uses State Anxiety from STAI (State-Trait Anxiety Inventory). The results of the study showed that the level of anxiety before treatment was severe anxiety (40%), moderate anxiety (40%), and mild anxiety (20%). Meanwhile, after being given treatment, the results were severe anxiety (3.3%), moderate anxiety (46.7%), and mild anxiety (50%). Based on the paired T test, the results showed that the average anxiety score of State before the Benson relaxation technique was 53.70±13.46 and after relaxation was 40.90± 8.16. The results of the paired T test showed a significance value of 0.000< (=0.05), it can be concluded that there is an influence of the difference in the average anxiety score of State before and after the Benson relaxation technique.